1966
DOI: 10.1002/1520-6807(196601)3:1<59::aid-pits2310030116>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of classroom social climate

Abstract: Many educators assume that positive classroom social climates enhance a pupil's mental health and his academic learning. The warm support, encouragement and respect which pupils show for one another facilitate high self-esteem and utilization of intellectual abilities. The influence which pupils feel they have in relation to peers, or the degree of competence a pupil sees himself as possessing also enhance his feelings about school and involvement in classroom tasks. In short, the relevance of positive classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…While a high degree of acceptance at the classroom level may indicate more cooperation, more affiliation and more effort, a low degree of peer acceptance is likely to be accompanied by other negative factors, such as competitiveness, conflict, and social comparisons. Classes with a low degree of acceptance are moreover likely to be characterized by poorer integration and poorer mutual support among the students . This may create a greater tendency for students to experience feelings of social inadequacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a high degree of acceptance at the classroom level may indicate more cooperation, more affiliation and more effort, a low degree of peer acceptance is likely to be accompanied by other negative factors, such as competitiveness, conflict, and social comparisons. Classes with a low degree of acceptance are moreover likely to be characterized by poorer integration and poorer mutual support among the students . This may create a greater tendency for students to experience feelings of social inadequacy.…”
Section: Discussionmentioning
confidence: 99%
“…Classes with a low degree of acceptance are moreover likely to be characterized by poorer integration and poorer mutual support among the students. 17 This may create a greater tendency for students to experience feelings of social inadequacy. It can also increase the perceived threat of victimization and other social sanctions in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Although longitudinal evidence is lacking, Schmuck (1966) found that unpopular children who also have few friends outside the classroom show poorer concurrent academic adjustment than unpopular children with more nonclass friends.…”
Section: Nature Of the Child's Social Relationshipsmentioning
confidence: 99%
“…Research has shown that classroom groups with supportive friendship patterns enhance academic learning, while more interpersonally tense class environments in which peer groups rejections are strong and frequent get in the way of learning (Schmuck, 1963;Schmuck, 1966;and Schmuck, 1971). These studies indicated that classroom peer groups characterized by a Volume XVI, Number 4 273 wide dispersion of friendships had more cohesiveness than groups with a concentration of liked and disliked members.…”
Section: Importance Of Peers For Learningmentioning
confidence: 99%